Historical and Linguocultural Analysis of Pathopsychological Terms with -Mania and -Phobia Term Elements - Popovych, Yaroslava (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article is devoted to the analysis of the origin of psychological clinical terminology and the impact on its development of historical, mythological and cultural realities/characters of Ancient Greece and Rome. Concerning that clinical terminology’s development took much time it has obviously made it harder to understand than those terms, that were recently composed. The application and understanding of «phobia» and «mania» in ancient authors’ original texts were analyzed to clarify whether the meaning and usage changed throughout the years. Among those text were works of the physicians Hippocrates and Areteus of Cappadocia, historian Pausanias and even philosophers Plato, Seneca, to see if the attitude to each term of those authors has changed in modern pathopsychic terminology. All the results of this study are summarized and represented in 10 categories, depending on the meaning of their attributive components, the origin of the term is analyzed and the corresponding linguistic and cultural commentary is given to it. Comments are related to mythological reality, which can make meaning of the term not clear to those, who are not aware of that specific myth and the historical and cultural features of Ancient Greece and Rome, which influenced the formation of each individual term. In addition, this article contains rare terms, that have -mania and -phobia component, and a similar first element. However, the language sources (Ancient Greek/ Latin) are different, that certify the development of this group of terms, for Latin is used in clinical terminology more rarely, than Greek.